Exploring Proficiency of Solving Mathematical Problem Among Mathematics Major - Ordiz, Joshua Edson Gorme; Costillas, Jasper Grant Tiempo (Universitas Ahmad Dahlan, 2023)
Learning problem-solving in mathematics was a challenge for both learners and teachers because of its complexity. Development of the skill necessitates understanding towards common observable predictors to depict the viable actions of typical students. This study created a model that determines the predictors' direct and indirect effects on mathematics problem-solving efficiency. It utilized predictive correlation design using multiple regression analysis to examine the hypothesized predictors. Results showed that self-efficacy and English proficiency did not directly influence the ability to perform in problem-solving; analytical-logical does otherwise. Notable findings displayed an inverse relationship of study habits among students. With that, improving analytical-logical skills promotes greater learning along with the development of English proficiency and self-efficacy. Furthermore, the study habits of mathematics majors were not meaningful because of the potential exposure to problem-solving.